2008
DOI: 10.1055/s-0028-1088307
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Tissue Distribution of the Sesquiterpene α-Humulene in Mice

Abstract: A quantitative study was undertaken to assess the plasma and tissue levels, tissue distribution and skin (ear) absorption of the sesquiterpene alpha-humulene, the main active constituent isolated from the plant Cordia verbenacea (Boraginaceae ), after oral, intravenous and topical administration in mice. The alpha-humulene levels were quantified by GC-MS analysis. The peak alpha-humulene concentration was achieved 15 min following its oral administration (150 mg/kg). Then, the alpha-humulene plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…These results suggest that passive diffusion is the main transport mechanism of all the sesquiterpenes tested across the Caco-2 cell monolayer and predict that they are the well-absorbed compounds in human intestine. Similar results were also found for some active sesquiterpenes, such as onitin [24], α-humulene [25], artemisinin [26] and parthenolide [27], which were all well-transported compounds by passive diffusion. The secretory permeability (P app BL→AP , 5.754 ± 0.817 × 10 −5 cm/s) of ICL was significantly higher than its absorptive permeability (P app AP→BL , 2.439 ± 0.505 × 10 −5 cm/s) and the ratio of P app AP→BL to P app BL→AP of ICL was 0.424 (l " Table 2), suggesting greater permeability in the BL to AP direction and the possible involvement of efflux transport [18].…”
Section: Resultssupporting
confidence: 78%
“…These results suggest that passive diffusion is the main transport mechanism of all the sesquiterpenes tested across the Caco-2 cell monolayer and predict that they are the well-absorbed compounds in human intestine. Similar results were also found for some active sesquiterpenes, such as onitin [24], α-humulene [25], artemisinin [26] and parthenolide [27], which were all well-transported compounds by passive diffusion. The secretory permeability (P app BL→AP , 5.754 ± 0.817 × 10 −5 cm/s) of ICL was significantly higher than its absorptive permeability (P app AP→BL , 2.439 ± 0.505 × 10 −5 cm/s) and the ratio of P app AP→BL to P app BL→AP of ICL was 0.424 (l " Table 2), suggesting greater permeability in the BL to AP direction and the possible involvement of efflux transport [18].…”
Section: Resultssupporting
confidence: 78%
“…It is found in herbs and spices such as hops, clove, basil, sage, ginger, spearmint, and ginseng as well as some fruits and vegetables. It has strong anti‐inflammatory properties comparable to dexamethasone systemically, topically, and in allergic airway inflammation, as well as anti‐nociceptive and analgesic properties . It has anti‐cancer activity, is anti‐bacterial including activity against Staphylococcus aureus , and insecticidal/larvicidal effects have been documented.…”
Section: Terpenes (Terpenoids)mentioning
confidence: 99%
“…Sharp had an LC 50 of 45.31 μg/mL in a brine shrimp test using three tumor cell lines. Chaves [61] determined that bioavailability of the sesquiterpene α-humulene in mice was as high as 18% when applied orally, and remained detectable up to 12 h after administration, and also showed that the compound was able to cross the blood-brain barrier which would explain the antinociceptive effects attributed to Cordia verbenacea DC.…”
Section: Function In Peoplementioning
confidence: 99%